Pengembangan Komoditas Manggis di Kabupaten Bogor berbasis Potensi Produksi, Ketersediaan dan Kesesuaian Lahan - Hanafi, Muhamad; Pravitasari, Andrea Emma; Sahara, Sahara (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Bogor Regency is one of the largest production areas of mangosteen in West Java. However, its mangosteen production fluctuated and tended to decline from 2016 to 2020 because of productive plant reduction. Meanwhile, this regency has a large area of non-productive land. The arrangement and development of new farms are required based on the potential of the existing ground. This study aimed to identify potential areas for mangosteen development based on harvesting area, production value, land availability, and suitability requirements. This research used the LQ, DLQ, Z-score, and geographic information system analysis using ArcGIS 10.8 based on overlay and limiting factors. Ranking regions are determined by the TOPSIS method. The results of the LQ-DLQ analysis explained that eight districts with superior and prospective categories existed. The results of the Z-score analysis show that the Klapanunggal and Babakan Madang sub-districts have lower productivity. At the same time, the types of land used for mangosteen are primarily dry land agriculture and production forests. Land suitability for mangosteen consists of land class S2 (quite suitable) with an area of 6,056.9 ha and class S3 (suitable marginal) with an area of 54,925 ha. The priority areas for developing mangosteen exports are Cigudeg, Leuwisadeng, Leuwiliang, Jasinga, Sukamakmur, Nanggung, Klapanunggal, and Babakan Madang. The western part of Bogor has more significant potential than the eastern one.